1996
DOI: 10.1007/bf00203783
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age, frailty and liver function on the pharmacokinetics of brofaromine

Abstract: Caffeine clearance, a simple, noninvasive test of CYP1A2 activity, is predictive of brofaromine clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Investigations into the effect of age on in vivo activity of CYP1A2, 3A4, 2C9, 2C19 and 2D6 generally report decreases, 18 although not for all substrates. For example, CYP1A2 activity is reported as both unchanged 19,20 and decreased 21,22 with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into the effect of age on in vivo activity of CYP1A2, 3A4, 2C9, 2C19 and 2D6 generally report decreases, 18 although not for all substrates. For example, CYP1A2 activity is reported as both unchanged 19,20 and decreased 21,22 with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…We had previously shown that CYP1A1-mediated EROD activity was lower in humans over 13 years of age; CYP1A2-mediated EROD was also shown to decrease with age [11]. A decrease in clearance of CYP1A2 substrate in the elderly was observed in other studies [12].…”
mentioning
confidence: 93%